2018
DOI: 10.3389/feart.2018.00015
|View full text |Cite
|
Sign up to set email alerts
|

Partial Melting of Lower Oceanic Crust Gabbro: Constraints From Poikilitic Clinopyroxene Primocrysts

Abstract: Cross-section of slow-spreading ridges, showing the different occurrences of melt in the oceanic crust (based on Sinton and Detrick, 1992; Dick et al., 2008). Gabbro s.l. includes troctolite, olivine-gabbro, gabbro, gabbronorite and ferrogabbro. Also dunite occurs along the Moho. Young hot crustal gabbro reacts (i.e., partial melting, hybridization, recrystallization) with invading primitive mantle-derived melt. Crystals, rocks and melt chemistry and texture are modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 81 publications
3
21
0
Order By: Relevance
“…This ratio is in rather good agreement with the dissolved Pl/Ol ratios determined by Yang et al (2019) and the faster dissolution of Pl compared to Ol suggested by Donaldson (1985). The equation itself is also consistent with AFC equations previously established from lower oceanic crust samples (e.g., Lissenberg and Dick, 2008;Leuthold et al, 2018). In addition, we used the REE partition coefficients calculated for the average compositions of Ol, Pl, and Cpx analyzed in the Lower unit using the composition-dependent models described above at 1,100°C.…”
Section: Evolution Of Melts Within the Lower Unitsupporting
confidence: 89%
See 1 more Smart Citation
“…This ratio is in rather good agreement with the dissolved Pl/Ol ratios determined by Yang et al (2019) and the faster dissolution of Pl compared to Ol suggested by Donaldson (1985). The equation itself is also consistent with AFC equations previously established from lower oceanic crust samples (e.g., Lissenberg and Dick, 2008;Leuthold et al, 2018). In addition, we used the REE partition coefficients calculated for the average compositions of Ol, Pl, and Cpx analyzed in the Lower unit using the composition-dependent models described above at 1,100°C.…”
Section: Evolution Of Melts Within the Lower Unitsupporting
confidence: 89%
“…The results show that Cpx Ti contents and Mg# expected after FC are both lower than the actual content of the minerals from both the Lower and the Upper unit ( Figure 8A). These geochemical signatures have already been interpreted as evidence for the occurrence of RPF in lower oceanic crustal sections (e.g., Lissenberg and Dick, 2008;Lissenberg and MacLeod, 2016;Leuthold et al, 2018). High-Mg# and Ti Cpx were also identified by Yang et al (2019) in the products of interaction experiments between MORB-type melts and a troctolite analog ( Figure 8A).…”
Section: Role Of Reactive Porous Flow In the Formation And Evolution mentioning
confidence: 55%
“…3). This small-scale heterogeneity can be explained by multiple replenishments in the crystal mush leading to dissolution-crystallization episodes 17 and juxtaposition of diverse populations of crystals 18 . At the grain scale, cores show more primitive compositions (higher Mg# in clinopyroxene and anorthite content in plagioclase) than rims (see Supplementary Fig.…”
Section: High Magnitude Small-scale Heterogeneity In Cumulate Mineralsmentioning
confidence: 99%
“…Further evidence is present in the plutonic sections of ophiolites (Basch et al, , ; Bédard, ; Bedard et al, ; Rampone et al, ; Sanfilippo, Tribuzio, et al, ). The samples revealed complex zoning patterns, reaction textures, and mineral compositions and modes that could not be explained by fractional crystallization: instead, the data suggest that melt‐mush reaction is a common process in the lower oceanic crust (Coogan, Saunders, et al, ; Dick et al, ; Gao et al, ; Leuthold et al, ; Lissenberg et al, ; Lissenberg & MacLeod, ; Meyer et al, ; Ridley et al, ). Such a melt‐mush reaction is also proposed to be common in continental magma systems (e.g., Bédard et al, ; Boudreau, ; Cashman et al, ; Irvine, ; Leuthold et al, ; Leuthold et al, ; Mathez, ; McBirney & Sonnenthal, ; Namur et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, melts and crystals coexist throughout the mid‐ocean ridge magma plumbing system, providing two possible mechanisms for reactions to occur between melts and crystals. The first is during the emplacement of primitive melts into the mush (Kvassnes & Grove, ; Leuthold et al, ). Primitive melts are unlikely to be saturated in (all of) the phases present in the mush in which they are emplaced, leading to partial melting reactions.…”
Section: Introductionmentioning
confidence: 99%